(untitled) (Historia Agraria de América Latina, 2023)
The present article attempts to re-centre and localise the inspection conducted by Potosí Corregidor and viceroy lieutenant don Pedro Osores de Ulloa in 1596 in the Tomina frontier, approaching the event through the political culture of the time. With the help of letters, reports of merits and services, and notarial records, the inspection is understood as the staging and renegotiation of multiple jurisdictions with the aim of preserving the frontier’s status quo. The inspection was not planned to alter the zone’s political dynamics but to confirm and strengthen the existing jurisdictions of the agents present in the area. The visita’s journey maps these jurisdictions and the political hierarchies that underpinned them.